Physicochemical properties of chemically activated empty fruit bunch biochars and their sorption capacities for pentachlorophenol as compared to a commercial activated carbon - Puvaneswaree, Nalaya; Samsuri, Abd. Wahid; Halmi, Mohd Izuan (Inderscience, 2022)
Chemical modification has been used to produce biochar composites with enhanced surface properties to adsorb organic contaminants efficiently. In the present study, the effectiveness of an empty fruit bunch biochar (EFBB) activated with hydrochloric acid (A-EFBB), sodium hydroxide (B-EFBB) and iron (III) chloride (Fe-EFBB) in adsorbing pentachlorophenol (PCP) as compared to the non-modified EFBB and a commercial activated carbon (AC) was investigated. The physicochemical properties of all the adsorbents were analysed and compared. The adsorption isotherm of PCP by all the adsorbents were fitted to the Freundlich and Langmuir adsorption isotherms. The maximum PCP adsorption capacity (Qmax) onto the adsorbents followed the ascending order of EFBB < Fe-EFBB < A-EFBB < B-EFBB < AC. These findings indicated that the NaOH activated EFBB had the potential for an alternative adsorbent of PCP removal from wastewater considering the high cost of AC.